Strategi Pengelolaan Kelas Blended Learning Dan Faktor Efisiensi Dalam Proses Pembelajaran Di Perguruan Tinggi - Nur Sa’adatul Fuadiyah; Hanif Abdul Rahman; Imam Syafi’i (JURNAL MANAJEMEN PENDIDIKAN, 2025)
BLENDED LEARNING CLASSROOM MANAGEMENT STRATEGIES AND EFFICIENCY FACTORS IN THE LEARNING PROCESS IN HIGHER EDUCATION Digitalization and technology have significantly impacted education, particularly blended learning models. This model combines offline and online learning, increasing flexibility and effectiveness using digital resources. However, blended learning poses challenges in adjusting to virtual or offline learning, adapting technology, and evaluating learning outcomes. Effectiveness in blended learning depends on infrastructure, such as technology, internet access, student engagement, and time management. Understanding these challenges and challenges can help develop solutions for optimal learning experiences for students. This study aims to analyze the effectiveness of blended learning and provide solutions for improved learning experiences. By using qualitative methods in the form of observations that focus on direct observation and interviews with several students.